2011
DOI: 10.1037/a0021240
|View full text |Cite
|
Sign up to set email alerts
|

Children's low affective perspective-taking ability is associated with low self-initiated pro-sociality.

Abstract: Children's affective perspective-taking (APT) may provide a basis for efficient social interaction. The APT abilities of 83 children from 46 same-sex sibling pairs (ages 36 to 72 months, M = 52.8; SD = 12.6) were assessed through their reactions to affectively loaded story situations, and children whose APT ability (but not general cognitive abilities) was low relative to other children of their age were designated as Low-APT children. These children were not less pro-social when specific social cues or reques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 20 publications
1
22
0
Order By: Relevance
“…First, children as young as 18 months of age show concern (as measured by their facial expression), even if the victim herself displays no emotion after a hurtful act (Vaish, Carpenter, & Tomasello, 2009). It has been suggested that in these contexts children can sympathize with others through some form of affective perspective-taking based upon situational cues, potentially drawing upon similar experiences in the past (Harris, 2008;Hoffman, 2000;Knafo, Steinberg, & Goldner, 2011;Vaish et al, 2009). Therefore, the current study indicates that children are able to make determinations in the context of goal-directed action, inferring from the situation that the other's goal is not met.…”
Section: Discussionmentioning
confidence: 99%
“…First, children as young as 18 months of age show concern (as measured by their facial expression), even if the victim herself displays no emotion after a hurtful act (Vaish, Carpenter, & Tomasello, 2009). It has been suggested that in these contexts children can sympathize with others through some form of affective perspective-taking based upon situational cues, potentially drawing upon similar experiences in the past (Harris, 2008;Hoffman, 2000;Knafo, Steinberg, & Goldner, 2011;Vaish et al, 2009). Therefore, the current study indicates that children are able to make determinations in the context of goal-directed action, inferring from the situation that the other's goal is not met.…”
Section: Discussionmentioning
confidence: 99%
“…The average of identification and justification across vignettes formed a composite to indicate overall APT. Previous studies using these vignettes reported inter-rater agreement ranging from .73 to .86 (Anastassiou-Hadjicharalambous & Warden, 2008a;Knafo et al, 2011;Strayer, 1993).…”
Section: Affective Perspective-taking (Apt)mentioning
confidence: 98%
“…Responses for emotion identification that were compatible with the correct emotion were scored 0.5 point (e.g., if the primary emotion depicted was sadness, and a possible secondary emotion was anger, sadness = 1 point, anger = 0.5 point). This scoring was adapted from Knafo, Steinberg, and Goldner (2011), who used this scoring system for a facial recognition task. A coding scheme was developed, and a random sample of 35% of cases was double-coded by an independent rater.…”
Section: Affective Perspective-taking (Apt)mentioning
confidence: 99%
“…The link between empathy and prosocial behaviors has long been established (Eisenberg and Fabes, 1990; Eisenberg and Miller, 1987), with recent work extending this to animal models (Ben-Ami Bartal et al, 2011; Decety et al, 2016; but see Vasconcelos et al, 2012). Developmentally, the association between empathy and prosociality emerges as early as 3 years in the human lifespan (Knafo et al, 2011) and persists past late adolescence (Carlson et al, 2015). Evidence from neuroimaging studies also converge on the importance of empathic, other-oriented concerns in predicting prosociality (e.g., FeldmanHall et al, 2015; Zaki and Mitchell, 2011).…”
Section: Prosocial Risk Takingmentioning
confidence: 99%